Home, school, and community collaboration : culturally responsive family involvement - Grant, Kathy B. 4 0 16; Ray, Julie; 5 (Los Angeles : Sage, 2010)
Offers strategies for kindergarten through twelfth grade teachers on effective partnering with classroom families and the community.
Includes bibliographical references (p. 396-423) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Home and school;Community and school;Parent-teacher relationships;Home and school;Community and school.;Parent-teacher relationship. -- United States.;United States.;United States.;United States; 20; 2